2021
DOI: 10.3390/molecules27010059
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Protective Effects of Lentil (Lens culinaris) Extract against Oxidative Stress-Induced Hepatotoxicity

Abstract: Excessive oxidative stress plays a role in hepatotoxicity and the pathogenesis of hepatic diseases. In our previous study, the phenolic extract of beluga lentil (BLE) showed the most potent in vitro antioxidant activity among extracts of four common varieties of lentils; thus, we hypothesized that BLE might protect liver cells against oxidative stress-induced cytotoxicity. BLE was evaluated for its protective effects against oxidative stress-induced hepatotoxicity in AML12 mouse hepatocytes and BALB/c mice. H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(34 reference statements)
2
13
0
Order By: Relevance
“…Our recent in vivo study indicated that LSHE stated substantial reductions in FBG in rats in a dose-dependent manner, as similarly indicated (13,23,51). These results strengthen our analysis, which confirms that LSHE possesses hypoglycemic effects because of rich polyphenols as effective antioxidants capable of modulating glucose levels (9,15). Practically, the administration of LSHE was extremely beneficial in body weight recovery in a dosedependent manner (57,61).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Our recent in vivo study indicated that LSHE stated substantial reductions in FBG in rats in a dose-dependent manner, as similarly indicated (13,23,51). These results strengthen our analysis, which confirms that LSHE possesses hypoglycemic effects because of rich polyphenols as effective antioxidants capable of modulating glucose levels (9,15). Practically, the administration of LSHE was extremely beneficial in body weight recovery in a dosedependent manner (57,61).…”
Section: Discussionsupporting
confidence: 87%
“…Our results demonstrated the efficacy of LSHE as a rich source of antioxidants that alleviated liver malfunctions and elevated serum lipids among CCl 4 -intoxicated rat groups. It might be due to increasing and supporting rats' serum with bioactive dietary antioxidants (9,15,62). Administration of LSHE at 50 or 100 mg GAE Kg −1 improved the lipid profile in dose-dependent manure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that oxidative stress occupied prominent values in the pathogenesis of hepatotoxicity ( Guo et al, 2019 ; Lv et al, 2020 ; Temel et al, 2020 ; Jung et al, 2021 ; Lim et al, 2021 ). When the body’s oxidation and anti-oxidation are out of balance, excess reactive oxygen species will be produced, resulting in a state of oxidative stress, lipid peroxidation of cell membranes, and abnormal organelle function ( Bao et al, 2010 ; Glade and Meguid, 2017 ; Hussein et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%